The Brasilia Rules: A case of interpretation by the Mexican Supreme Court of Justice of the Nation on the age of older adults as a condition of vulnerability - Barreto Nova, Óscar Guillermo (2023)
This paper begins with the question: Do the Brasilia Rules have jurisdictional value for Mexican judges? The Supreme Court of Justice of the Nation cleared this question when it resolved a case about older adults; however, was the decision correct? This text will analyze a case in which the highest court ruled on whether the Brasilia Rules are binding for judges when resolving cases. The methodology chosen to develop the work was partly that of the case method, in which the case heard by the Mexican Court was approached. In addition to the above, the arguments of the parties are reflected upon, in order to later question whether the decision taken regarding the vulnerability of the elderly due to their age, a condition foreseen in the Brasilia Rules, was correct.